PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PENDIDIKAN PANCASILA PADA SISWA KELAS II SD MUHAMMADIYAH 8 JAGALAN SURAKARTA - Wihida, Refianti; Widyasari, Choiriyah; Faridawati, Lina; Arifah, Irma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to find out whether the use of the Make A match learning model can increase the activeness and learning outcomes of Pancasila Education in class II students at SD Muhammadiyah 8 Jagalan Surakarta. The research subjects were 22 grade II students at SD Muhammadiyah 8 Jagalan. This research is classroom action research. Meetings were held over 2 cycles. The research results showed an increase in student activity and learning outcomes. From the indicator of activeness in asking questions from pre-cycle, 8 (36.36%) students became 14 (63.64%) students in cycle I then became 19 (86.36%) in cycle II. Answering questions from pre-cycle 10 (45.45%) students became 16 (72.73%) students in cycle I then became 19 (86.36%) in cycle II. Expressing pre-cycle opinions, 8 (36.36%) students became 13 (59.10%) students in cycle I then became 18 (81.82%) in cycle II. Student learning outcomes at the pre-cycle stage were 45.45% (10 students reached KKM). In cycle 1 stage it increased to 68.18% (15 students reached KKM). In the second cycle stage it increased to 81.82% (18 students reached the KKM). The conclusion of this research is that learning by applying the Make A Match model can increase the activeness and learning outcomes of Pancasila Education in class II students at SD Muhammadiyah 8 Jagalan.